Effect of Nutrition Education Using Digital Flipchart Media on Nutritional Knowledge and Eating Pattern Among Adolescents at Metro School Makassar - Ummul Mujaahidah; Mushawwir Taiyeb; Rachmawaty; Firdaus Daud; Andi Asmawati Azis (PT. Global Research Collaboration, 2026)
Adolescence is a critical period for establishing lifelong dietary habits, yet nutritional knowledge among Indonesian adolescents remains inadequate. This study aimed to examine the effect of nutrition education using digital flipchart media on nutritional knowledge and eating patterns among adolescents at Metro School Makassar. A quasi-experimental design with a pretest-posttest control group was employed, involving 90 adolescents divided equally into an experimental group (digital flipchart) and a control group (PowerPoint). Data were collected using a 30-item multiple-choice nutritional knowledge test and a 40-item eating pattern questionnaire adapted from the WHO Global School-based Student Health Survey (GSHS), the Youth Risk Behavior Surveillance System (YRBSS), and the Food Frequency Questionnaire (FFQ). Data were analyzed using descriptive statistics and the independent sample t-test following normality (Shapiro-Wilk) and homogeneity (Levene) tests. Results showed that the experimental group achieved a mean posttest nutritional knowledge score of 25.82 (SD = 1.749), with 91.1% of students categorized as